Features of genetic algorithm for plain text encryption - Abduljabbar, Riyadh Bassil; Hamid, Oday Kamil; Alhyani, Nazar Jabbar (International Journal of Power Electronics and Drive Systems/International Journal of Electrical and Computer Engineering, 2021)
The data communication has been growing in present day. Therefore, the data encryption became very essential in secured data transmission and storage and protecting data contents from intruder and unauthorized persons. In this paper, a fast technique for text encryption depending on genetic algorithm is presented. The encryption approach is achieved by the genetic operators Crossover and mutation. The encryption proposal technique based on dividing the plain text characters into pairs, and applying the crossover operation between them, followed by the mutation operation to get the encrypted text. The experimental results show that the proposal provides an important improvement in encryption rate with comparatively high-speed Processing.